EDTA enhances cementum-like tissue formation, TGF-β1 & VEGF in rat molars during regenerative endodontics - Reis-Prado, Alexandre Henrique Dos; Silva, Isabela Joane Prado [UNESP]; Goto, Juliana [UNESP]; Machado, Nathália Evelyn da Silva [UNESP]; Avelar, Gleide Fernandes de; Albergaria, Juliano Douglas Silva; Szawka, Raphael Escorsim; Bottino, Marco Cícero; Cintra, Luciano Tavares Angelo [UNESP]; Ervolino, Edilson [UNESP]; Ribeiro-Sobrinho, Antônio Paulino; Benetti, Francine (FapUNIFESP (SciELO), 2025)
This study investigated the influence of ethylenediaminetetraacetic acid (EDTA) irrigation on cementum-like tissue formation and TGF-β1, FGF-2, and VEGF immunolabeling during regenerative endodontic procedures (REPs) in immature rat molars. The lower first molars of 12 four-week-old male rats (80 g) underwent pulpectomy in the mesial canal and were randomly categorized into two experimental groups (n = 6): sodium hypochlorite (NaOCl) - irrigated for 5 min with 2.5% NaOCl; and NaOCl-EDTA - irrigated with 2.5% NaOCl, followed by 5 min of 17% EDTA. After inducing bleeding with a size 10 K-file, the cavities were sealed. Untreated molars served as control-15d (n = 3) and immediate control (n = 3). Either immediately or after 15 days, the animals were euthanized, and the teeth were collected for histomorphometric and immunohistochemical (TGF-β1, FGF-2, and VEGF) analysis. The results were analyzed by the Mann-Whitney U-test (p < 0.05). Histomorphometric analysis revealed increased cementum-like tissue formation in the NaOCl-EDTA group compared with that in the NaOCl group (p < 0.05). Regarding growth factor immunolabeling, the NaOCl-EDTA group exhibited enhanced TGF-β1 and VEGF immunolabeling in the root tip area and the center region of the apical third of the pulp tissue, compared with that in the NaOCl group (p < 0.05); however, no significant difference was observed in FGF-2 (p > 0.05). In conclusion, the use of EDTA in REPs positively affected the formation of cementum-like tissue and TGF-β1 and VEGF in the apical region but did not influence FGF-2.